Reviving Public Service Delivery at the Grassroots through Public-Private Partnership in Nigeria’s Fourth Republic - Oyewo, Oyekunle Oluseye (ABUAD Journal of Social and Management Sciences, 2023)
The paper examines the performance of local governments in Nigeria with special reference to their service delivery responsibilities. Local government is described as a veritable instrument of socio-economic development at the grassroots and it was for this purpose that it became constitutionally recognised as a level of government through the 1976 Local Government Reform. However, the capacity of the Nigerian local governments to carry out responsibilities assigned to them has been jaundiced by the unbridled attack on their finances by higher public authorities, particularly state governments. Specifically, local governments’ share of revenue from the federation account and other sources of revenue have regrettably been annexed by the state governments, thereby reducing local authorities to governments on papers only. Using the secondary sources of data, the article examines how local government service delivery responsibilities can be resuscitated through the Public-Private Partnership (PPP) arrangement. The paper revealed general absence of standard framework for the adoption of PPP to tap into the available huge private investment for public service delivery at the grassroots. The paper recommends active collaboration of the stakeholders in grassroots development toward developing a standard framework for PPP to restore the status of Nigerian local governments as primary providers of public services.